TEMPERATURE MEASUREMENT COMPUTATIONS IN SURFACE SURFACE WITH DIFFERENT METHODS - Masduki Zakarijah (Jurnal Penelitian Saintek, 2003)
This research goal  to heat  transfer rate prediction  on  every node  insurface  line  and  the  difference  of  temperature  measurement  between direct measurement and numerical analysis based on Matlab with finite difference technique. Object of this research is aluminium plate to take shape a plaid square with size 5 x 22 em to divided in 75 node. The result of this research is heat transfer rate on every node in surface line between direct  measurement  and  numerical   analysis   based   on  Matlab  not difference of significance.